Optimizing foaming agent concentration and recycled fine aggregate content to enhance mechanical and durable properties of foam concrete mixes - Rodhia R.; Sahdeo S.K.; Kumar B. (My University, 2025)
This research explores the impact of using recycled fine aggregates from construction and demolition wastes (CD-RFA) through the replacement of natural sand in proportion of 0 %, 10 %, 30 %, 50 %, 70 %, and 100 % for making foam concrete mixes. Protein based foaming agent was diluted with water in ratios of 1:20, 1:40 and 1:60. It was found that with the increase in the proportion of recycled fines, the porosity, sorptivity and water absorption of foam concrete mixes increases significantly. At the same time, a downward trend in the mechanical characteristics was noted. However, the obtained values of compressive strength, flexural strength, and split tensile strength of 22.35, 5.68 and 2.27 MPa were found to be well within the ACI 523 R 2014 recommended ranges of 8–22, 3–6.4 and 1–2.2 MPa, respectively. Hardened density, abrasion resistance, and resistance to sulphates and chlorides attack showed perceptible decline. The present study recommends the replacement of natural sand up to 50 % with CD-RFA. The foam concrete mix prepared using recycled fines will help clearance of a large quantities of CD wastes, thereby benefiting the environment and ecology. © 2024 Elsevier Ltd